COVID-19 in a Child With Transposition of the Great Arteries S/P Fontan Palliation: A Case Report and Literature Review - Wen, Chen; Shi, Guocheng; Liu, Wei; Zhang, Hao; Lin, Gangxi; Chen, Huiwen (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Although adult patients with cardiovascular disease are at higher risk of adverse outcomes such as death or severe infection, limited data exist regarding pediatric patients with congenital heart disease. We would like to report our experience with COVID-19 in a pediatric patient with Fontan circulation. Furthermore, we present a review of patients with Fontan palliation and COVID-19 previously reported in the literature to summarize the clinical characteristics of this population. Case Presentation: A 9-year-old boy with dextro-transposition of the great arteries, ventricular septal defect, pulmonary stenosis, patent foramen ovale and borderline left ventricle post bidirectional Glenn shunt and Fontan palliation presented with paroxysmal cough in the context of COVID-19. Coagulation profile was beyond the normal limits and the patient began to receive anticoagulant aspirin. On the 5th day, the patient presented with fever, sore throat and fatigue. The oxygen saturations dropped to 93%, and he received nasal catheter oxygen inhalation. On the 7th day, computed tomography of the chest revealed little emerging flaky exudation in the posterior basal segment of the left lower lobe. Nasal cannula was removed on the 12th day and coagulation profile returned to normal on the 16th day. After two consecutively negative SARS-CoV-2 viral RNA test (on the 18th and 19th days, interval ≥ 24 hours), he was discharged from hospital on the 21st day. Literature review indicated that COVID-19 with Fontan palliation seemed to be more common in male adults. Disease presentation varied from mild upper respiratory tract infection to severe pneumonia. Complications were not uncommon in this population. The treatments varied depending on the specific factors. Fortunately, most patients reported a favorable prognosis. Conclusion: Although patients with COVID-19 and Fontan circulation might have the risk of adverse outcomes due to multiple mechanisms, most patients have a favorable prognosis.